Does Oil Dependence Affect Regional Wealth? A Regional Study for the Municipalities of the State of Rio de Janeiro - Tavares, Felipe de SÃ¡; Almeida, Alexandre; Postali, Fernando (International Journal of Energy Economics and Policy, 2021)
The aim of this study is to analyze the regional effects of oil royalty dependence on the local economic development of municipalities of the Rio de Janeiro state. To do so, we used spatial econometric models to estimate the local and spillover effects of royalty dependence on the economic local product. The main results were derived based on the Spatial Autoregressive Combined model (SAC) estimated by Generalized Moments (GM). The study’s contribution is to address the natural resource curse debate through its regional perspective by estimating the direct, spillover, and total effects of oil royalty dependence on economic product, which is a groundbreaking approach for the natural resource curse debate. The results show that both the direct and spillover effects are negative and significant, indicating that there is evidence of the presence of a regional natural resource curse in the municipalities of the Rio de Janeiro state. Keywords: Spatial Econometrics; Natural Resource Curse; Econometrics; Spillover effects; Spatial Panel Data Models; Method of Generalized Moments JEL Classifications: C33, E69, N56. DOI: https://doi.org/10.32479/ijeep.11737